Epistemological Beliefs about Physics Learning: The Role of Gender, Grade Level, and Ethnicity Background toward Quality and Inclusive Education - Oktavina Pandango; Sentot Kusairi; Sujito (Postgraduate, University of Mataram, 2026)
This study explores high school students' epistemological beliefs about physics learning in East Nusa Tenggara (NTT) Province and evaluates the effects of gender, grade level, and ethnicity. Utilizing a descriptive-quantitative survey design, the study involved 390 science students (grades 10–12) across six high schools. Data were gathered via the validated Beliefs and Attitudes Toward Physics and Learning (BAPL) instrument and analyzed using a three-way ANOVA. The overall average BAPL score was . Statistics revealed that gender significantly impacted overall beliefs (F = 3.99, p = 0.05), with females reporting more positive baseline scores (70.00 6.74) than males (68.55 7.34). Grade level also exerted a significant main effect (F = 3.60, p = 0.04), showing more sophisticated views in higher grades. Conversely, the main effect of ethnicity was highly insignificant (F = 0.006, p = 0.94). While no significant overall three-way interaction was found (F = 0.85, p = 0.43), a dimension-specific three-way interaction emerged exclusively within the Relevance of Physics in Everyday Life (RLE) dimension (F = 3.05, p = 0.05). These findings suggest that uniform school systems act as epistemic equalizers across ethnic backgrounds in NTT, though gender-sensitive and context-aware pedagogy remains essential to foster sophisticated physics beliefs.